Genome-wide identification and characterization of HSP90 family gene in cotton and their potential role in salt stress tolerance - Hao, Zhao Yan; Feng, Qian; Man, Xu Yan; Qi, Dong Qi; Qing, Yu Shi; Yang, Zhai Wei; Elbagory, Mohssen; Kasem, Esam Sayed; Yasir, Muhammad; Rong, Jiang Yu (Frontiers in Plant Science, 2025)
Heat shock proteins 90 (HSP90s) are conserved molecular chaperones essential for cellular homeostasis under abiotic stress. While several studies have been reported to elucidate the role of HSP90s in heat stress responses in cotton, their involvement in salt stress remains underexplored. Gossypium hirsutum L. is highly susceptible to salt stress. The Current study investigated the evolutionary aspects, expression patterns, and functional validation of HSP90 family members in cotton under salt stress. A comprehensive genomic analysis of G. hirsutum, G. raimondii, and G. arboreum, identified 56 HSP90 genes which were classified into three distinct phylogenetic groups. Gene structure and motifs analysis revealed a conserved nature of HSP90s within each group. Additionally, cis-acting elements suggested the potential roles of HSP90s in biotic and abiotic stresses. The Ka/Ks ratio of all genes was < 1 suggesting negative and purifying selection pressure during molecular evolution. Expression analysis demonstrated the potential role of HSP90 genes in salt tolerance. Notably, out of ten HSP90 genes five genes exhibited highly differential expression under salt stress, as confirmed by qRT-PCR analysis. Moreover, virus-induced silencing of the two salt stress-responsive genes, Ghir_D03G016230 and Ghir_D02G013530, which were upregulated under salt stress, resulted in a significant decrease in SOD, POD, and CAT, accompanied by a marked increase in MDA content in the salt-tolerant cotton cultivar. These findings provide novel insights into the functional roles of HSP90s in G. hirsutum under salt stress.